2011
DOI: 10.2337/dc11-1242
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Is Associated With a Poor Response to Intravenous Thrombolysis in Acute Ischemic Stroke

Abstract: OBJECTIVEInsulin resistance (IR) may not only increase stroke risk, but could also contribute to aggravate stroke prognosis. Mainly through a derangement in endogenous fibrinolysis, IR could affect the response to intravenous thrombolysis, currently the only therapy proved to be efficacious for acute ischemic stroke. We hypothesized that high IR is associated with more persistent arterial occlusions and poorer long-term outcome after stroke thrombolysis.RESEARCH DESIGN AND METHODSWe performed a prospective, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 23 publications
7
49
0
1
Order By: Relevance
“…The association between insulin resistance and prognosis of patients with ischemic stroke has rarely been studied. Recent results from Calleja et al8 (n=109) and Bas et al9 (n=108) showed that insulin resistance was associated with worse outcome in patients with acute ischemic stroke who were treated with intravenous thrombolysis. A preliminary report from Hishinuma et al including 32 patients with stroke without history of diabetes mellitus showed that 3 of 4 patients with recurrent events had insulin resistance 10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between insulin resistance and prognosis of patients with ischemic stroke has rarely been studied. Recent results from Calleja et al8 (n=109) and Bas et al9 (n=108) showed that insulin resistance was associated with worse outcome in patients with acute ischemic stroke who were treated with intravenous thrombolysis. A preliminary report from Hishinuma et al including 32 patients with stroke without history of diabetes mellitus showed that 3 of 4 patients with recurrent events had insulin resistance 10.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that insulin resistance is associated with an increased risk of coronary heart disease and stroke in the nondiabetic population 3, 4, 5, 6, 7. Recent studies have also shown that insulin resistance is associated with worse outcomes in patients with acute ischemic stroke who are treated with intravenous thrombolysis 8, 9. Few studies, however, have focused on the clinical outcome of general ischemic stroke 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycemia is known to be a strong determinant of poor outcome in stroke patients in general [27], and also in ischemic stroke patients treated with intravenous thrombolysis [28]. In this context, not only admission's glycemia predicts stroke outcome, but hyperglycemia observed at any time within the first 48 hours may have a deleterious effect on stroke patients (5,6). In order to explain the independent association found between GIP and outcome, we hypothesize that GIP expression in the setting of acute ischemic stroke might be a part of an insulin-sensitizing response aimed to reduce glucose level, thus counteracting the adverse effect of acute hyperglucemia on stroke outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously reported that insulin resistance, the proposed key pathophysiological mechanism underlying metabolic syndrome [5], is associated with a worse response to intravenous thrombolysis in acute ischemic stroke [6]. In that study, insulin resistance was measured by means of the HOMA index calculated during admission.…”
Section: Introductionmentioning
confidence: 99%